(untitled) (Al-Qamar, 2023)
Islamic banking is a financial system that adheres to the principles of Sharia law, which prohibits the charging of interest. Scholars have differing perspectives on Islamic banking, with some arguing that it is a more ethical and sustainable form of banking, while others contend that it is not truly interest-free or transparent. This paper critically examines the perspectives of various scholars on Islamic banking as presented in HEC recognized journals. First school of thought, represented by Dr. Fazlurrehman, distinguishes between riba and commercial interest. They do not consider commercial interest to be riba, and therefore believe that conventional banking is not in conflict with Islamic teachings. A second school of thought, represented by Mufti Taqi Usmani, Prof. Khurshid Ahmed, and others, advocates for the Islamization of the conventional banking system. They believe that banks can be modified in accordance with Islamic teachings to create a more ethical and interest free financial system. On the other hand, Mufti Rashid Ahmed and Mufti Dr. Abdul Wahid, views Islamic banking as a positive development for Muslims, but does not believe that the current Islamic banking system is fully based on Islamic law. They have proposed suggestions for how the system can be made more acceptable. A third school of thought, represented by Dr Muhammad Zahid Siddique Mughal and others, completely rejects Islamic banking. They argue that there is no real difference between conventional and Islamic banking. There are many reasons why scholars have different opinions about Islamic banking. One reason is that there are different arguments presented in Islamic law about the prohibition of interest. Another reason is that there are different methods of Islamic banking and scholars have different opinions about these methods. These opinions vary depending on social, and economic factors. However, there is no doubt that it is a growing field, with Islamic banks operating in over 75 countries around the world.